Las habilidades de la lecto-escritura en el aprendizaje significativo en los niños (as) de cuarto año de educación básica de la escuela Isabel la Católica del Recinto Cuatro Esquinas, Cantón Guaranda Provincia Bolívar en el año lectivo 2017– 2018. - Alvarez Alvarez, Mercy Del Rocio (2018)
The aim of the research work is to explore and optimize the teaching-learning process that literacy provides, and to propose to teachers a methodological guide that helps to improve meaningful learning and, therefore, academic performance during the school year. To obtain data, a diagnosis was made through an observation guide, a focus group with the parents and an interview with the teacher in charge of the fourth grade of basic education of the institution that was analyzed, which allowed us to detect and 10 get deeper into the problem under study, to propose activities that are designed to overcome the deficiency of reading and writing, taking into account the interests and needs of children. It was concluded that the application of techniques with readings in a comprehensive way is a way to improve academic performance, that is why the proposal of a methodological guide is made, for the strengthening of the reading and writing, towards the improvement of the academic performance, the same that frames the possible solution to the problem.